Localisation of gamma-ray bursts from the combined SpIRIT+HERMES-TP/SP nano-satellite constellation. (8th February 2023) - Thomas, M.; Trenti, M.; Sanna, A.; Campana, R.; Ghirlanda, G.; Řípa, J.; Burderi, L.; Fiore, F.; Evangelista, Y.; Amati, L.; Barraclough, S.; Auchettl, K.; et al.
Abstract: Multi-messenger observations of the transient sky to detect cosmic explosions and counterparts of gravitational wave mergers critically rely on orbiting wide-FoV telescopes to cover the wide range of wavelengths where atmospheric absorption and emission limit the use of ground facilities. Thanks to continuing technological improvements, miniaturised space instruments operating as distributed-aperture constellations are offering new capabilities for the study of high-energy transients to complement ageing existing satellites. In this paper we characterise the performance of the upcoming joint SpIRIT and HERMES-TP/SP constellation for the localisation of high-energy transients through triangulation of signal arrival times. SpIRIT is an Australian technology and science demonstrator satellite designed to operate in a low-Earth Sun-synchronous Polar orbit that will augment the science operations for the equatorial HERMES-TP/SP constellation. In this work we simulate the improvement to the localisation capabilities of the HERMES-TP/SP constellation when SpIRIT is included in an orbital plane nearly perpendicular (inclination = 97.6 ° ) to the HERMES-TP/SP orbits. For the fraction of GRBs detected by three of the HERMES satellites plus SpIRIT, we find that the combined constellation is capable of localising 60% of long GRBs to within ${\sim}30\, deg^{2}$ on the sky, and 60% of short GRBs within ${\sim}1850\, deg^{2}$ ( $1σ$ confidence regions), though it is beyond the scope of this work to characterise or rule out systematic uncertainty of the same order of magnitude. Based purely on statistical GRB localisation capabilities (i.e., excluding systematic uncertainties and sky coverage), these figures for long GRBs are comparable to those reported by the Fermi Gamma Burst Monitor instrument. These localisation statistics represents a reduction of the uncertainty for the burst localisation region for both long and short GRBs by a factor of ${\sim}5$ compared to the HERMES-TP/SP alone. Further improvements by an additional factor of 2 (or 4) can be achieved by launching an additional 4 (or 6) SpIRIT-like satellites into a Polar orbit, respectively, which would both increase the fraction of sky covered by multiple satellite elements, and also enable localisation of ${≥} 60%$ of long GRBs to within a radius of ${\sim}1.5^{°}$ (statistical uncertainty) on the sky, clearly demonstrating the value of a distributed all-sky high-energy transient monitor composed of nano-satellites.